Fetomaternal Complications of Rh-Negative Blood Group - Khalil, Sobia; Humayun, Aiysha; Syed, Wajeeha; Naz, Nabeela (Indus Journal of Bioscience Research, 2025)
Objective: To determine the frequency of fetomaternal outcomes in Rh-negative pregnant patients. Research Design: A descriptive study. Duration and Place of Study: The study was conducted in the Department of Obstetrics and Gynecology at Lady Reading Hospital, Peshawar, from August 15, 2023, to February 15, 2024. Methodology: This study included 133 women aged 18–40 years with singleton pregnancies, a gestational age of >28 weeks, and Rh-negative blood type. Women with congenital anomalies or who refused consent were excluded. Data on demographic details, such as age, gestational age, and parity, were collected, along with fetomaternal outcomes like cesarean section, oligohydramnios, neonatal anemia, stillbirth, and neonatal jaundice. Results: The mean age of participants was 27.77 years, with a mean gestational age of 36.52 weeks and a mean parity of 1.44. The most common fetomaternal complication was cesarean section (56.4%), followed by neonatal anemia (12%), neonatal jaundice (11.3%), oligohydramnios (6.8%), and stillbirth (4.5%). Stratification revealed significant associations between gestational age and complications: neonatal anemia and stillbirth were more prevalent in later gestations (>36 weeks), while oligohydramnios was more common in earlier gestations (28–36 weeks). Conclusion: Rh-negative pregnancies are associated with various fetomaternal complications, including cesarean section, neonatal anemia, jaundice, and stillbirth. Gestational age plays a significant role in determining the prevalence of these complications.